Differential remodeling of carotid artery in spontaneously hypertensive and hereditary hypertriglyceridemic rats - Cebová, Martina; Kristek, František; Kuneš, Jaroslav (Physiological research, 2006)
High blood pressure, increased level of cholesterol, diabetes, hypertriglyceridemia and obesity are risk factors accompanied metabolic syndrome. The aim of the study was to compare geometry of carotid artery (AC) of 3-week-old (3w) and 52-week-old (52w) hereditary hypertriglyceridemic rats (hHTG) and spontaneously hypertensive rats (SHR) which represent a genetic model of human essential hypertension with age-matched Wistar rats. After sacrificing the rats were perfused with a glutaraldehyde fixative under the pressure 90 mm Hg (3w) and 120 mm Hg (52w) for 10 min via cannula placed into left ventricle. Middle part of AC was excised and processed according to standard electron microscopy procedure. Geometry of AC was evaluated in light microscopy. SHR vs. Wistar rats: BP of 3w did not differ, in 52w it was increased; cardiac hypertrophy was found in both ages; wall thickness (WT) and cross sectional area (CSA) in 3w did not differ, in 52w both were increased; inner diameter (ID) in 3w and 52w was decreased; WT/ID was increased in both ages. Hereditary HTG vs. Wistar rats: BP was increased in both periods; cardiac hypertrophy was observed in 3w; WT in 3w was decreased, in 52w it was increased; CSA and ID were decreased in both ages; WT/ID was increased only in 52w. Discrepancies between development of BP, cardiac hypertrophy in SHR and hHTG rats were observed. Alterations of BP were not in harmony with alterations in geometry of carotid arteries in both SHR and hHTG rats. We suggest that BP is not the main stimuli evoked hemodynamic and structural alterations of cardiovascular system in ontogenic development of SHR and hHTG rats.
Keywords: krysa rodu Rattus; Animals; Hypertriglyceridemia; potkani inbrední SHR; hypertenze; arteriae carotides; mužské pohlaví; zvířata; Hypertension; Carotid Arteries; Male; Rats, Wistar; Rats; Rats, Inbred SHR; hypertriglyceridemie; potkani Wistar